Opinion Leader versus New Opinion Leader dalam Komunikasi Pemasaran (Studi Kasus Selebtwit di Twitter untuk Komunikasi Pemasaran) - Hananto, Prio (Interaksi: Jurnal Ilmu Komunikasi, 2014)
The concept of ‘opinion leaders’ in the traditional media, they can express their opinion by using mass media channels. For example, Lazarsfeld, Berelson, and Gaudet (1948) suggested that the ‘opinion leaders’, which actively collect information that is sent from the media, insert the values and their own view into the information, and then pass it on to consumers around them in hari.Twitter daily life has become a new means of communication in the era of new media or the internet era, and it is possible to come up with new criteria for opinion leaders in social media. By observation, researchers are trying to get a more in-depth picture of whether there is a difference between opinion leaders in traditional media with new media.